The Malays in Australia : Language, Culture, Religion - Asmah Omar, Dato', Prof. Emeritus, Dr., 1940-, author 181420 (Kuala Lumpur : Dewan Bahasa Dan Pustaka, 2008)
The Malays in Australia: Language, Culture, Religion focuses on the three aspects of life which make up Malay identity: language, culture or way of life, and religion. Although these three features are upheld in the day-to-day life of the Malays in the Australian milieu, religion seems to override the other two, However, the Malays seem to have a strategy of their own in seeing that the children learn the Malay language, the language of their ancestors, and that is by teaching the Islamic religion in that language and not in English. The Malays in Australia are those whose home countries are Malaysia, Indonesia, and Singapore. They came to their adopted country with different purposes, and from different social backgrounds. The different social groups live in different communities, and members of each group tend to be drawn to those with the same social background as themselves. From this aspect, national differences in terms of their countries of origin are not important. Migrant Malays in other parts of the world may have the same aspirations as those in Australia in being loyal to their adopted country, not forgetting their heritage which is rooted in their homeland. But what makes this study of Malay migration to Australia interesting is the picture of different patterns of migration from the Malay world to mainland Australia and the Indian Ocean Territories. Such patterns are not found in Malay migration to other parts of the world. As a linguist, the author cannot but give emphasis to the question of language compared to that of culture and religion. The movement of the speakers of a particular language to settle down in a new land may eventually lead to the formation of an area of spread for this language, and this means an extension of the geolinguistics of the language concerned. This has happened to Malay in Australia, but the status of the Malay language communities here in terms of the use of the language in a culture alien to it cannot be equated to the status of the Malay language in the Malay world where the language area of spread is the same as the culture area that can be attributed to the Malays. On this basis, the author has termed the areas of Malay language spread in Australia as non-traditional areas of spread compared to the traditional areas which are located in the Malay world. The typology of areas of language spread is extended further by a comparison of the Malay communities in the various places in terms of the intensity of use, the type of Malay language variety that characterizes each community, and the time-depth in the new land that vanes from the community to community. Malays, like other races, have migrated from their traditional World to other continents and formed communities, though small compared to other migrant communities like the Chinese and the Indians. This book is a story about them in the new milieu.